2019
DOI: 10.24990/injec.v3i1.196
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Sodium Intake, Physical Activities and Psychological Problems of Patients Suffering from Hypertension in Rural and Urban Areas

Abstract: Introduction: The patients suffering from hypertension require treatment to prevent the complications by performing both pharmacological and non-pharmacological hypertension management. This research aims at revealing the difference of sodium intake, physical activities, and psychological problems in patients suffering from hypertension in rural and urban areas. Methods: This descriptive-quantitative research employs a cross sectional design. The research was conducted at Gondokusuman Community Health Center 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The Riskesdas report in 2013 showed that the prevalence of self-reported hypertension among adults in Yogyakarta was 25.7% [ 5 ]. Previous studies in Yogyakarta province revealed that risk factors for hypertension were obesity, intake of fruits and vegetables [ 10 ], physical activity and anxiety levels [ 11 ]. Several studies showed that factors associated with hypertension among the Indonesian adult population were age [ 12 , 13 ], low education, overweight or obesity and health care utilization in the last month [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Riskesdas report in 2013 showed that the prevalence of self-reported hypertension among adults in Yogyakarta was 25.7% [ 5 ]. Previous studies in Yogyakarta province revealed that risk factors for hypertension were obesity, intake of fruits and vegetables [ 10 ], physical activity and anxiety levels [ 11 ]. Several studies showed that factors associated with hypertension among the Indonesian adult population were age [ 12 , 13 ], low education, overweight or obesity and health care utilization in the last month [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For study settings, in quantitative and mixed-method studies, 10 studies took place nationally, 24 , 41 , 47–51 , 53 , 63 , 64 19 in the urban areas, 20 , 21 , 23 , 31–33 , 36–38 , 40 , 42 , 44–46 , 52 , 54 , 55 , 58 , 76 16 in rural areas, 22 , 25–29 , 34 , 39 , 43 , 56 , 57 , 59–62 , 75 and two studies in multiple settings. 30 , 35 For quantitative studies, four of them were conducted in urban settings, 66 , 67 , 70 , 71 five were in the rural area 65 , 69 , 72–74 and one study could not be specified. 68 Overall, thirteen 22 , 26–29 , 32 , 42 , 45 , 57–60 , 64 studies have the mean age of older people as the participants (60 years old and above), whereas the rest of the studies were adults 18 years and older.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the body system in the elderly is due to the aging process resulting to decreased ability of the elders for physical activity and changes in their physical appearance affect the elder's social and economic life (Pangastuti et al, 2019). This situation is a stressor that can lead to negative feelings for the elderly that is having the feeling of helplessness, uselessness, frustration, despair, sadness and feelings of isolation, that often cause and lead to their minimal interactions with others on total withdrawal from others.…”
Section: Introductionmentioning
confidence: 99%